2022
DOI: 10.3389/fvets.2022.883295
|View full text |Cite
|
Sign up to set email alerts
|

Identification of microRNA Transcriptome Involved in Bovine Intramuscular Fat Deposition

Abstract: BackgroundIntramuscular fat deposition in beef is a major determinant of carcass quality and value in the USA. The objective of this study was to examine changes in microRNA (miRNA) transcriptome that are involved with intramuscular fat deposition with time-on-concentrates (TOC). Yearling steers were individually fed a high concentrate diet and changes in intramuscular fat deposition were monitored by real-time ultrasound at 28 to 33 d intervals. Longissimus muscle biopsies collected on d 0, 92 and 124 TOC to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Regarding the role of transcription factors and miRNAs, beef cattle, sheep and pigs all involve PPARγ, miRNAs and other transcription factors in regulating lipid metabolism and IMF content (Duckett & Greene, 2022; Feng et al., 2022; Han et al., 2021). While these commonalities exist, there are differences in how these factors operate in each species.…”
Section: Comparative Genomics With Other Livestock Speciesmentioning
confidence: 99%
“…Regarding the role of transcription factors and miRNAs, beef cattle, sheep and pigs all involve PPARγ, miRNAs and other transcription factors in regulating lipid metabolism and IMF content (Duckett & Greene, 2022; Feng et al., 2022; Han et al., 2021). While these commonalities exist, there are differences in how these factors operate in each species.…”
Section: Comparative Genomics With Other Livestock Speciesmentioning
confidence: 99%
“…Further, the Protein–Protein Interaction (PPI) prediction analysis indicated that the PVALB gene was the highest hub gene. Susan K. Duckett [ 20 ] demonstrated that bta-miR-122 may be related to IMF deposition by conducting miRNA transcriptome sequencing on bovine longissimus dorsi muscle tissue. By transcriptome sequencing analysis of chicken pectoral and abdominal muscles, Na Luo [ 21 ] reported that the IMF deposition in pectoral muscles was associated with pyruvate and citrate metabolism through genes such as GAPDH , LDHA , GPX1 , and GBE1.…”
Section: Introductionmentioning
confidence: 99%